YouTube Video Popularity in Iraq and Neighboring Countries - Zaid Mundher (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
YouTube is a leading global video platform offering highly diverse content. Analyzing regional user behavior on this platform provides valuable strategic insights. This study examines YouTube video popularity in Iraq, Saudi Arabia, Turkey, and the United States, highlighting cross-cultural content consumption patterns. Using the YouTube Data API, metadata including video titles, views, likes, and comments were collected over a 30-day period. Exploratory data analysis revealed significant regional differences in user engagement rates, preferred content categories, and platform interaction durations. The findings provide actionable insights for marketers, content creators, and researchers interested in digital sociology and localized online user behavior.